2006
DOI: 10.1016/j.jcrs.2006.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Hyperopic shift in refraction associated with implantation of the single-piece Collamer intraocular lens

Abstract: The most likely etiology was the development of anterior capsule fibrosis, sometimes exacerbated by a small capsulorhexis, which could cause the IOL to move posteriorly, resulting in a hyperopic change in refraction. Previous in vitro testing by the manufacturer ruled out a change in the refractive power of the IOL in the eye as a cause of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 5 publications
1
35
0
2
Order By: Relevance
“…A symmetric, wellcentered, and appropriately sized anterior capsulotomy is essential for maximizing IOL performance, and this is even more critical for premium IOLs (ie, toric, multifocal, and accommodating IOLs). The ability to produce a perfect capsulotomy for any IOL design is extremely valuable since capsulotomy construction directly influences the ELP, 14,19 which is a major source of error in IOL power calculations. 20 The actual axial position of the IOL is significantly influenced by the configuration of the capsulorhexis.…”
Section: Discussionmentioning
confidence: 99%
“…A symmetric, wellcentered, and appropriately sized anterior capsulotomy is essential for maximizing IOL performance, and this is even more critical for premium IOLs (ie, toric, multifocal, and accommodating IOLs). The ability to produce a perfect capsulotomy for any IOL design is extremely valuable since capsulotomy construction directly influences the ELP, 14,19 which is a major source of error in IOL power calculations. 20 The actual axial position of the IOL is significantly influenced by the configuration of the capsulorhexis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The phenomenon of delayed hyperopic shift following cataract surgery has been described after implantation of a single-piece Collamer plate-haptic IOL (CC420BF, Staar Surgical Co.) with a minimum incidence of 0.02%. 8,9 With this IOL, the mean hyperopic shift in affected cases was 1.81 D (range 0.25 to 3.75 D) occurring between 1 week and 11 months after surgery. The cases described were associated with a small capsulorhexis, secondary phimosis of the capsulorhexis, and posterior displacement of the IOL.…”
Section: Discussionmentioning
confidence: 86%
“…The cases described were associated with a small capsulorhexis, secondary phimosis of the capsulorhexis, and posterior displacement of the IOL. 8,9 The authors noted that posterior bowing of the IOL was associated with a gap between the IOL and anterior capsule, 9 and they also concluded that the syndrome was due to posterior migration of the IOL following capsule contraction and phimosis. 8,9 These cases along with our observations suggest that this is a generic problem associated with IOL designs that have very flexible haptics.…”
Section: Discussionmentioning
confidence: 99%
“…If the capsulotomy is too small, fibrosis and hyperopic shift may ensue. 31 Conversely, if too large or asymmetric, the IOL may be adversely affected by tilt, rotation, decentration, myopic shift, and posterior capsular opacification. 21,32,33 The capsulotomy is also closely related to the effective lens position (ELP) and it has been found that imprecise estimation of the ELP is the single biggest cause of inaccurate IOL power calculation.…”
Section: Anterior Capsulotomymentioning
confidence: 99%